Dermatologic care of sexual and gender minority/LGBTQIA youth, Part 2: Recognition and management of the unique dermatologic needs of SGM adolescents. Issue 5 (1st July 2019) - Kosche, Cory; Mansh, Matthew; Luskus, Mark; Nguyen, Andy; Martinez‐Diaz, Gabriel; Inwards‐Breland, David; Yeung, Howa; Boos, Markus D.
Abstract: Sexual and gender minority (SGM) individuals, including lesbian, gay, bisexual, transgender/gender diverse, questioning/queer, intersex, and asexual (LGBTQIA) persons, represent a historically underserved population within the field of medicine, though their unique health needs are increasingly recognized. Part 2 of this two‐part review will address unique concerns regarding acne, tanning behavior, sexually transmitted infections, and other health disparities among SGM adolescents. A more comprehensive understanding of the dermatologic needs of SGM youth will better allow pediatric dermatologists to actively and compassionately care for this health disparity population.